TEACHING ENGLISH TO MIGRANTS IN PEKANBARU: ADVANTAGES AND DISADVANTAGES OF BEING NON L1 SPEAKER TEACHER IN MULTILINGUAL CLASSROOM - Dewi Sari Wahyuni (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Teaching English in Non English Speaking Countries needs a bigger effort for the little expose availability. As an Indonesian who teaches English to Indonesian, the writer still faces some difficulties. Therefore, it is a great challenge and opportunity that when International Organization of Migration assigns the writer to teach English to migrants from Afghanistan, Iran, Iraqi, Syria, Palestine, Pakistan, Somalia, Sudan, Myanmar and even Sri Lanka. English is a media for communicating in multicultural environment such as detention house and community housings where these migrants stay before they are sent to their destination country or deported to their country of origin. The courses are done in Pekanbaru, Indonesia. As Non Native English Speaker, the writer gets used to teaching classroom to students with similar mother tounge. It is not easy, indeed, to deal with students from different countries who are diverse in languages. As the show must go on, the writer learns by doing. From arranging materials to the approaches have gone trials and errors. No matter how big the challenge is there are always be advantages and disadvantages that should be anticipated by the writer as teacher. In this paper, the writer will talk about her perspectives on the advantages and disadvantages of being not able to communicate in students first language in multilingual English Classroom.